HIV Health literacy beyond the biomedical model: an innovative visual learning tool to highlight the psychosocial complexities of care. Issue 12 (2nd December 2022) - Hollingdrake, Olivia; Howard, Chris; Lui, Chi-Wai; Mutch, Allyson; Dean, Judith; Fitzgerald, Lisa
ABSTRACT: The HIV care continuum represents a linear clinical pathway from testing to viral suppression; however, it does not capture the psychosocial complexities of contemporary HIV care. We developed an innovative and appealing visual learning resource to extend the scope of HIV health literacy beyond biomedical constructs. Based on the lived experiences of recently diagnosed people living with HIV in Queensland, the "Journeys through the HIV Care Continuum" Map presents the continuum as a complex journey incorporating challenges such as poor health literacy, health service access and stigma alongside facilitators to care, including emotional and peer support. Designed for audiences who may not access academic literature, the Map can be used to facilitate conversations between recently diagnosed people living with HIV and peer navigators, and as a learning tool for health professionals, carers and students. The Map highlights opportunities to support PLHIV in meaningful ways that will reduce stigma and promote care access.